Diagnosis Komunitas sebagai Upaya Pengendalian Hipertensi di Desa Teluknaga Kabupaten Tangerang - Dhio D W; Rani L; M. Iqram; Ashira G; Silvana Tirtasari (Universitas Malahayati Lampung, 2026)
ABSTRACT Hypertension remains a major public health problem worldwide and represents one of the leading contributors to cardiovascular morbidity and mortality. Community diagnosis is a systematic approach to identifying priority health problems and their determinants at the population level, serving as a foundation for targeted public health interventions. This study aimed to describe the implementation of community diagnosis and evaluate health education and blood pressure screening interventions as an initial effort to reduce hypertension cases in Teluknaga Village, the working area of Teluknaga Public Health Center, Tangerang Regency. A descriptive community-based study was conducted from September to November 2025. Epidemiological, demographic, and health service data were collected from the public health center records. Problem prioritization was performed using the Urgency–Seriousness–Growth (USG) method, supported by the Blum health determinant paradigm and fishbone analysis. Interventions consisted of health education on hypertension and blood pressure screening. Knowledge improvement was assessed using pre-test and post-test questionnaires, while blood pressure status was mesured using standardized procedures. Hypertension was identified as the most prevalent disease, accounting for 22% of total hypertension cases in the study area, with Teluknaga Village reporting the highest number of cases. Among 36 participants, 63.8% showed an increase of at least 10 points in post-test scores, and all participants achieved post-test scores above 80. Blood pressure screening detected pre-hypertension and varying stages of hypertension, enabling early counseling and referral. Hypertension is a priority health problem in Teluknaga Village. Community diagnosis-based interventions, particularly health education and early detection through blood pressure screening, demonstrate potential as an effective initial strategy for hypertension control at the community level. Keywords: Community Diagnosis, Hypertension, Health Education, Blood Pressure Screening, Primary Health Care. ABSTRAK Hipertensi merupakan salah satu masalah kesehatan utama yang berkontribusi terhadap peningkatan morbiditas dan mortalitas kardiovaskular. Diagnosis komunitas merupakan pendekatan sistematis untuk mengidentifikasi masalah kesehatan prioritas beserta determinannya di tingkat populasi sebagai dasar perencanaan intervensi kesehatan yang terarah. Penelitian ini bertujuan untuk menggambarkan pelaksanaan diagnosis komunitas serta mengevaluasi intervensi edukasi kesehatan dan skrining tekanan darah sebagai upaya awal pengendalian hipertensi di Desa Teluknaga, wilayah kerja Puskesmas Teluknaga, Kabupaten Tangerang. Penelitian deskriptif berbasis komunitas dilaksanakan pada periode September–November 2025. Data epidemiologi, demografi, dan pelayanan kesehatan diperoleh dari Puskesmas Teluknaga. Prioritisasi masalah dilakukan menggunakan metode Urgency–Seriousness–Growth (USG) dengan pendekatan paradigma determinan kesehatan Blum dan analisis fishbone. Intervensi berupa edukasi kesehatan hipertensi dan skrining tekanan darah dilakukan kepada masyarakat. Evaluasi peningkatan pengetahuan dilakukan melalui pre-test dan post-test, sedangkan status tekanan darah diukur menggunakan prosedur standar. Hipertensi merupakan penyakit terbanyak di wilayah kerja Puskesmas Teluknaga, dengan Desa Teluknaga mencatat proporsi kasus tertinggi. Sebanyak 63,8% peserta mengalami peningkatan skor pengetahuan ≥10 poin dan seluruh peserta memperoleh nilai post-test di atas 80. Skrining tekanan darah menunjukkan sebagian besar peserta berada pada kategori pra-hipertensi dan hipertensi. Hipertensi merupakan masalah kesehatan prioritas di Desa Teluknaga. Pendekatan diagnosis komunitas yang dikombinasikan dengan edukasi kesehatan dan skrining tekanan darah berpotensi menjadi strategi awal yang efektif dalam pengendalian hipertensi berbasis komunitas. Kata Kunci: Diagnosis Komunitas, Hipertensi, Edukasi Kesehatan, Skrining Tekanan Darah, Pelayanan Kesehatan Primer.